Cancer Surgery 2.0: Guidance by Real-Time Molecular Technologies. Issue 6 (June 2021) - Ogrinc, Nina; Saudemont, Philippe; Takats, Zoltan; Salzet, Michel; Fournier, Isabelle
Abstract : In vivo cancer margin delineation during surgery remains a major challenge. Despite the availability of several image guidance techniques and intraoperative assessment, clear surgical margins and debulking efficiency remain scarce. For this reason, there is particular interest in developing rapid intraoperative tools with high sensitivity and specificity to help guide cancer surgery in vivo . Recently, several emerging technologies including intraoperative mass spectrometry have paved the way for molecular guidance in a clinical setting. We evaluate these techniques and assess their relevance for intraoperative surgical guidance and how they can transform the future of molecular cancer surgery, diagnostics, patient management and care. Highlights: Cancer surgery is the first treatment in many solid tumors. Quality of the initial surgery has a strong influence on the patient outcome. Tumors must be excised at best, but accurate delineation of their edges and margin definition is a huge challenge. Presently, the practice is the intraoperative examination of surgical specimens by the pathologist through morphological examination of stained tissue sections. However, this is far from satisfactory and subjected to an important error rate. New technologies are emerging for intraoperative assessment, such as traditional tools (US, MRI, and CT) and new modalities (OCT, Raman spectroscopy, and MS). MS provides the molecular fingerprint of the tissues and molecules appear advantageously as distinct signals. Several MS systems have been developed for intraoperative analysis; for example, iKnife, SpiderMass, and MassSpecPen, which have already been showcased in the operating theater.